2013
DOI: 10.1007/s12529-013-9315-0
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Symptoms, Sleep Duration, and Disability Pensions: a Prospective Study of Swedish Workers

Abstract: Background Previous studies have found insomnia and long sleep duration to be independently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Our finding that a one unit increase in job control was independently associated with a decreased risk of DP due to mental diagnoses confirms earlier studies (11)(12)(13)(14)(15)(16)(17)(18)(19)51). However, the results that each one unit increase, rather than a decrease, in job demands or social support predict a higher risk of DP contradict those of previous findings (13,17,31,52).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our finding that a one unit increase in job control was independently associated with a decreased risk of DP due to mental diagnoses confirms earlier studies (11)(12)(13)(14)(15)(16)(17)(18)(19)51). However, the results that each one unit increase, rather than a decrease, in job demands or social support predict a higher risk of DP contradict those of previous findings (13,17,31,52).…”
Section: Discussionsupporting
confidence: 83%
“…One explanation for these contradictory results may be the application of a validated JEM (20)(21)(22), while the majority of other studies (11,(15)(16)(17)(18)(19) used individually reported data on experiences of such exposures. Also, previous studies have mainly studied these working conditions as categorical (median split, quartiles) rather than as continuous variables and have, therefore, only been able to capture variation within the different categories (11,(15)(16)(17)(18)(19)47). Another explanation is that since the information about psychosocial working conditions was based on sector-based occupations, adjusting for occupation to account for the influence of socioeconomic status was not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination of symptom may be the result of a peculiar etiopathology or of the presence of different, concomitant factors. Previous studies reported sleep onset insomnia increasing the risk for debilitating mental problems (Canivet et al, 2014) while neuroimaging brings evidence of a connection between early morning awakenings and depression (Stoffers et al, 2012;Yu et al, 2018). Speculatively, it is possible that the two insomnia symptoms and depression are connected in a consecutive and escalating manner.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown how individuals experiencing trouble with sleep onset were about three times more likely than good sleepers to receive a disability pension due to a mental condition. This risk was higher than for other nocturnal symptoms of insomnia (Canivet et al, 2014). In a recent study we reported that difficulties initiating sleep alone plays a leading role in rising anxiety levels and different combinations of symptoms concur with different strengths of anxiety symptoms (Bragantini et al, 2019).…”
Section: Introductionmentioning
confidence: 89%